2001
DOI: 10.1091/mbc.12.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Action on GLUT4 Traffic Visualized in Single 3T3-L1 Adipocytes by Using Ultra-fast Microscopy

Abstract: A novel imaging technology, high-speed microscopy, has been used to visualize the process of GLUT4 translocation in response to insulin in single 3T3-L1 adipocytes. A key advantage of this technology is that it requires extremely low light exposure times, allowing the quasi-continuous capture of information over 20-30 min without photobleaching or photodamage. The half-time for the accumulation of GLUT4-eGFP (enhanced green fluorescent protein) at the plasma membrane in a single cell was found to be of 5-7 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
90
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 48 publications
(61 reference statements)
16
90
2
Order By: Relevance
“…The present findings are consistent with recent studies that document a requirement of intact F-actin for optimal GLUT4 translocation in response to insulin in both primary (23) and cultured adipocytes (13,18,19,21,24). Interestingly, previous findings (18,24) indicated the inhibition of insulin-stimulated GLUT4 recycling by actin depolymerization reagents such as latrunculin B is about 50%, similar to our present findings with dominant negative N-WASP (Fig.…”
Section: Fig 3 Effects Of N-wasp Mutants On Insulin-induced Corticasupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings are consistent with recent studies that document a requirement of intact F-actin for optimal GLUT4 translocation in response to insulin in both primary (23) and cultured adipocytes (13,18,19,21,24). Interestingly, previous findings (18,24) indicated the inhibition of insulin-stimulated GLUT4 recycling by actin depolymerization reagents such as latrunculin B is about 50%, similar to our present findings with dominant negative N-WASP (Fig.…”
Section: Fig 3 Effects Of N-wasp Mutants On Insulin-induced Corticasupporting
confidence: 93%
“…Interestingly, previous findings (18,24) indicated the inhibition of insulin-stimulated GLUT4 recycling by actin depolymerization reagents such as latrunculin B is about 50%, similar to our present findings with dominant negative N-WASP (Fig. 5).…”
Section: Fig 3 Effects Of N-wasp Mutants On Insulin-induced Corticasupporting
confidence: 93%
“…On the other hand, while there is a controversy on the mechanism of action of nocodazole especially in 3T3-L1 adipocytes (14,15,16,19,20), our results show that nocodazole has no direct inhibitory effect on the glucose transporter activity (Fig. 10).…”
Section: Discussionmentioning
confidence: 53%
“…While the role of the actin filaments in insulin-induced GLUT4 translocation has been reported with relatively consistent results (10 -13), the relevance of the microtubules to the insulin action has been controversial. Thus, depolymerization of the microtubules caused a complete cessation of the basal linear tracking movements of green fluorescent protein (GFP)-tagged GLUT4, and inhibited insulin-induced GLUT4 translocation and glucose uptake by 40 -70% in 3T3-L1 adipocytes (14,15). Likewise, Olson et al (16) also showed that nocodazole treatment of 3T3-L1 adipocytes resulted in about 80% inhibition of insulin-stimulated translocation of GLUT4.…”
mentioning
confidence: 95%
“…The cytoskeleton plays a significant role in facilitating GLUT4 exocytosis mediated by both microtubules and actin filaments (5)(6)(7)(8)(9). Microtubules direct the transport of GLUT4 vesicles to the cell cortex via the kinesin motor protein KIF5B (10).…”
mentioning
confidence: 99%